Towards selective modulation of the carotid sinus nerve as a therapeutic approach for metabolic diseases - Roque, Irina Gaião (2023)
Metabolic disorders such as type 2 diabetes (T2DM) affect millions of individuals globally, but therapeutic strategies are limited. Recently, it has been shown that bioelectronic modulation of the carotid sinus nerve (CSN) reversed T2DM in rats. However, the carotid body (CB) has other physiological functions, requiring selective modulation that does not interfere with these functions. Thus, this thesis aims to 1) characterize the activity of CSN in response to glucose and insulin administration, 2) identify electrophysiological markers of metabolic disease in the CSN, and 3) decompose the in-vivo CSN activity. The results show that: 1) the CSN activity is correlated with metabolic function; that hypercaloric (HFHSu) diet has caused changes in the metabolism, and in the activity of CSN in basal conditions, and in response to glucose; administration of insulin caused alterations in CSN activity, but its effect diminish with subsequent doses; 2) the time between bursts or frequency of these may be neuronal biomarkers to distinguish the metabolic condition, and trace changes in glycemia; 3) there are three possible components to represent the chemoreceptor activity of CB that in the in-vivo recordings present a wider frequency range in their spectrums. Moreover, the hypercaloric diet promoted changes in the spectrum of some of the common components found in the recordings for both preparations. To conclude, this work advances knowledge of the relationship of neuronal activity of the CSN and metabolic condition, thus opening new perspectives for the selective modulation of CSN.